Asuhan Kebidanan Pada Balita Dengan Gizi Kurang di BPM Suratmi Kota Batam - Wilda Yunita; Silvia Mona; Susanti Susanti (Pusat riset dan Inovasi Nasional, 2024)
Children are one of the age groups that are very vulnerable to nutritional problems. Nutritional problems do not only occur when the mother is pregnant, nutritional problems also arise during infancy. The occurrence of nutritional problems in infants, namely, allergies to food ingredients, excess nutrition or obesity, and diarrhea can lead to malnutrition which has the potential to cause poor nutritional status and even malnutrition. This case report aims to carry out midwifery care for under-fives with malnutrition comprehensively and sustainably through the SOAP documentation approach. Case collection was carried out by conducting patient home visits. Conclusion of midwifery care An. A with poor nutrition, after carrying out midwifery care for 3 visits to the patient, the results obtained in the last study were an increase in weight in An. A from 9.2 to 9.7 kg body weight but still in the stage of undernourishment with the KMS curve status category according to BW/U is in yellow. The community is expected to comply with posyandu visits so that the growth and development of children can be monitored. For health services to be able to provide education to the public about the importance of monitoring the growth and development of children to avoid the incidence of malnutrition.